WORLD INNOVATION RATINGS AND THEIR IMPACT ON THE ECONOMIC DEVELOPMENT OF UKRAINE - SMIRNOVA, Daryna; PIROGOV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes Ukraine's innovation potential in the context of globalization and identifies key factors that influence its development. It also assesses Ukraine's positions in international innovation activity rankings, particularly the Global Innovation Index, European Innovation Scoreboard, and Bloomberg Innovation Index. The dynamics of changes in Ukraine's indicators in these rankings are studied, and the main trends and challenges affecting the country's competitiveness in the global innovation environment are identified.The analysis results indicate that the country has significant scientific and technological potential, which, however, remains insufficiently realized due to several barriers. Among the main problems are identified: insufficient funding for scientific research, weak innovation infrastructure, insufficient integration of science and business, and low level of state support for innovation projects, as well as the negative impact of political instability and military operations on the territory of Ukraine. It is established that, despite difficult macroeconomic conditions, the country demonstrates a high level of educational potential and active development of the IT sector, which creates prospects for improving its international rankings.Particular attention is paid to the analysis of the Global Innovation Index, according to which Ukraine lost positions after 2020. The best results were achieved in the field of knowledge and technology, while the worst indicators were in the field of infrastructure and market environment. The deterioration of Ukraine's position in the Bloomberg rating was also noted, which is due to a decrease in investment in innovation and the instability of the business environment.Directions for improving state innovation policy are proposed, including: increasing funding for scientific research, developing innovation infrastructure, promoting international scientific and technical cooperation, supporting technological startups, and improving public-private partnership mechanisms. Prospects for increasing Ukraine's competitiveness through active involvement in European innovation programs and stimulating integration into global scientific initiatives are outlined.
Keywords: innovation; globalization; analytics; innovation potential